Perception of Hospital Pharmacist on Working Performance in Yogyakarta Province, Indonesia - Dona Muin; Satibi Satibi; Susi Ari Kristina; Yayi Suryo Prabandari (Universitas Airlangga, 2023)
Background: Pharmacists support the success of hospital in efforts to improve people's quality of life then the performance measurement of pharmacists is carried out. Objectives: This study aimed to measure pharmacist performance based on the perception of pharmacists working in hospitals. Methods: Perception surveys were conducted with pharmacists working in public hospitals. The assessment was performed using a closed questionnaire that was proven to be valid and reliable. This study evaluated pharmacists' perceptions of their work performance and their ability to perform their roles, duties, and functions in the hospital. A total of 192 pharmacist respondents answered 61 statements in the questionnaire that were divided into 11 dimensions as follows:1) the objectives set; 2) following the procedure; 3) initiatives; 4) performing the main task; 5) the ability to cooperate; 6) out implementing pharmaceutical standards; 7) the potential for solving problems; 8) quick response; 9) self-competence; 10) the ability to take verbal orders and writing; and 11) endurance at work. Results: The various answers of respondents to the questionnaire led to the conclusion that pharmacists' performance in hospitals is included in the high-performance category. Conclusion: This study showed that pharmacists have a high perception of their ability to work, as outlined in their assessment of their work performance in hospitals. Pharmacists' perceptions of their workplace performance in public hospitals are useful for developing pharmaceutical services. The results of this study are expected to provide a basis for improving the performance of pharmacists working in hospitals, especially hospitals in the Yogyakarta area.